2019
DOI: 10.3390/cancers11070945
|View full text |Cite
|
Sign up to set email alerts
|

6-Thioguanine and Its Analogs Promote Apoptosis of Castration-Resistant Prostate Cancer Cells in a BRCA2-Dependent Manner

Abstract: Background: Mutations in the oncosuppressor gene BReast CAncer susceptibility gene 2 (BRCA2) predispose to aggressive forms of prostate cancer which show poor response to taxane-based therapy, the standard treatment for castration-resistant, aggressive prostate cancer. Herein, we addressed the question whether changes in BRCA2 expression, a potential surrogate marker for BRCA2 activity, may affect the response of castration-resistant prostate cancer cells to 6-thioguanine (6-TG), a thiopurine used in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The compound had no detrimental effects on HUVEC viability under normal or high glucose conditions at all the doses tested. This is in line with the previous evidence reporting 6TG as able to promote apoptosis only in cancer cells ( Laera et al, 2019 ; Li et al, 2020 ). In particular, 5 µM 6TG significantly increased the cell viability of HUVECs exposed to high glucose and also reduced their vasculogenic activity, confirming its anti-angiogenic effects previously reported in endothelial cells or the chick embryo chorioallantoic membrane, as well as in AML patients showing a reduced bone marrow microvessel density when treated with 6TG ( Padró et al, 2000 ; Presta et al, 2002 ; Dean, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…The compound had no detrimental effects on HUVEC viability under normal or high glucose conditions at all the doses tested. This is in line with the previous evidence reporting 6TG as able to promote apoptosis only in cancer cells ( Laera et al, 2019 ; Li et al, 2020 ). In particular, 5 µM 6TG significantly increased the cell viability of HUVECs exposed to high glucose and also reduced their vasculogenic activity, confirming its anti-angiogenic effects previously reported in endothelial cells or the chick embryo chorioallantoic membrane, as well as in AML patients showing a reduced bone marrow microvessel density when treated with 6TG ( Padró et al, 2000 ; Presta et al, 2002 ; Dean, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, TG has been tested in both non-small cell lung cancer [45] and recurrent small cell lung cancer [46] but no clinical response was observed in these patients. Recently, interest in TG has risen again, promising preliminary results were found in prostate cancer [47]. Furthermore, TG was widely investigated for the treatment of glioma and showed positive results in patients who failed conventional chemoradiotherapy [48][49][50][51][52][53][54][55].…”
Section: Oncology and Hematologymentioning
confidence: 99%
“…The loss of MTAP expression has been linked to a tumor-promoting effect in multiple cancers, and MTAP may serve as a tumor suppressor ( 28 – 30 ). For example, in 2021, Han et al.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of MTAP expression has been linked to a tumorpromoting effect in multiple cancers, and MTAP may serve as a tumor suppressor (28)(29)(30). For example, in 2021, Han et al found that 9p21 loss, normally CDKN2A (13.5%) and MTAP (9.3%), confers a cold tumor immune microenvironment, poor clinical outcomes, and primary resistance to immune checkpoint therapy for cancers (31).…”
Section: Discussionmentioning
confidence: 99%